Checkpoint inhibitor therapy for cancer in solid organ transplantation recipients: an institutional experience and a systematic review of the literature. Issue 1 (16th April 2019) - Abdel-Wahab, Noha; Safa, Houssein; Abudayyeh, Ala; Johnson, Daniel H.; Trinh, Van Anh; Zobniw, Chrystia M.; Lin, Heather; Wong, Michael K.; Abdelrahim, Maen; Gaber, A. Osama; Suarez-Almazor, Maria E.; Diab, Adi
Abstract : Background: Checkpoint inhibitors (CPIs) have revolutionized the treatment of cancer, but their use remains limited by off-target inflammatory and immune-related adverse events. Solid organ transplantation (SOT) recipients have been excluded from clinical trials owing to concerns about alloimmunity, organ rejection, and immunosuppressive therapy. Thus, we conducted a retrospective study and literature review to evaluate the safety of CPIs in patients with cancer and prior SOT. Methods: Data were collected from the medical records of patients with cancer and prior SOT who received CPIs at The University of Texas MD Anderson Cancer Center from January 1, 2004, through March 31, 2018. Additionally, we systematically reviewed five databases through April 2018 to identify studies reporting CPIs to treat cancer in SOT recipients. We evaluated the safety of CPIs in terms of alloimmunity, immune-related adverse events, and mortality. We also evaluated tumor response to CPIs. Results: Thirty-nine patients with allograft transplantation were identified. The median age was 63 years (range 14–79 years), 74% were male, 62% had metastatic melanoma, 77% received anti-PD-1 agents, and 59% had prior renal transplantation, 28% hepatic transplantation, and 13% cardiac transplantation. Median time to CPI initiation after SOT was 9 years (range 0.92–32 years). Allograft rejection occurred in 41% of patients (11/23 renal, 4/11 hepatic, and 1/5 cardiac transplantations), at similar rates for anti-CTLA-4 and anti-PD-1 therapy. The median time to rejection was 21 days (95% confidence interval 19.3–22.8 days). There were no associations between time since SOT and frequency, timing, or type of rejection. Overall, 31% of patients permanently discontinued CPIs because of allograft rejection. Graft loss occurred in 81%, and death was reported in 46%. Of the 12 patients with transplantation biopsies, nine (75%) had acute rejection, and five of these rejections were T cell-mediated. In melanoma patients, 36% responded to CPIs. Conclusions: SOT recipients had a high allograft rejection rate that was observed shortly after CPI initiation, with high mortality rates. Further studies are needed to optimize the anticancer treatment approach in these patients.